A design case of chain reaction: Creative Gears Laboratory. Issue 1 (1st June 2014) - Liao, Guan-Ze
The design case presents the developed chain reaction game Creative Gears Laboratory based on problem-solving situations. The entire process of chain reaction consists of various scientific components, such as gear devices and tool modules, and game scenarios are created. There are ten sets of tool modules designed as referring operational behaviours in chain reaction games. The problem-solving situations in the chain reaction game designed four game scenarios: Risk Precaution, Obstacle Elimination, Situation Balance and Confidence Challenges. There were sixteen topical situations created by brainstorming methods and related solutions of scenarios based on problem-solving situations. The future study will conduct the narrative interview to investigate on the cognitive process during problem-solving procedure.